Quality improvement project on the development of a management algorithm for iatrogenic perforations and the long-term impact on physician knowledge - Lew, Daniel; Abboud, Yazan; Picha, Suellen M.; Lai, Ellis C.; Park, Kenneth H.; Pandol, Stephen J.; Almario, Christopher V.; Lo, Simon K.; Gaddam, Srinivas (Endoscopy International Open, 2022)
Abstract Background and study aims Acute iatrogenic endoscopic perforations (AIEPs) can have high morbidity and mortality, especially colonic perforations. Knowledge of diagnosis and AIEP management can improve patient care. The aims of this study were to: develop an evidence-based AIEP management algorithm; study its short-term and long-term impact on physician knowledge; and evaluate physician knowledge using hypothetical clinical scenarios. Methods An institutional AIEP management algorithm was created using the most current recommendations from the American Society for Gastrointestinal Endoscopy and the European Society of Gastrointestinal Endoscopy. Input from advanced endoscopists, nurses, and anesthesiologists was also obtained. We assessed change in physician knowledge using a 10-item questionnaire before (pretest), a standardized one-page AIEP educational material and algorithm immediately after (post-test) to test short-term retention, and 6 months later (6-month reassessment) to test long-term retention. With the 6-month reassessment, two clinical scenarios based on real AIEP were presented to evaluate application of knowledge. Results Twenty-eight subjects (8 gastroenterology fellows and 20 practicing gastroenterologists) participated in the assessments. Pretest and immediate post-test accuracies were 75 % and 95 % ( P < 0.01), respectively. Six-month reassessment accuracies were 83.6 %, significantly worse compared to post-test accuracies ( P < 0.05), but significantly improved compared to pretest accuracies ( P < 0.05). Accuracies for clinical scenarios #1 and #2 were 67.5 % and 60.3 %, respectively. Fellows had similar accuracies when compared to practicing gastroenterologists. Conclusions Using standardized methodology and a multidisciplinary approach, an AIEP management algorithm was created to improve patient care and alleviate physician and staff stress. In addition, we showed that a one-page educational document on perforations can significantly improve short-term and long-term physician knowledge, although periodic reeducation is needed.